1995
DOI: 10.1071/bt9950273
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CO2 Enrichment on Water Relations in Maranthes corymbosa and Eucalyptus tetrodonta

Abstract: Seeds of Maranthes corymbosa Blume and Eucalyptus tetrodonta F.Muell were sown under ambient or CO2 enriched conditions (two replicate tents per treatment) in tropical Australia and allowed to grow, rooted in the ground, for 20 months. For both species, periodic measurements of leaf water potential, stomatal conductance and leaf temperature were made on four replicate leaves on each of four replicate trees within each tent. Measurements were made in November (M. corymbosa) and June (E. tetrodonta). At the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 15 publications
4
22
0
Order By: Relevance
“…This could lead to a reduction in soil water depletion due to reduced canopy-scale transpiration, which could sustain transpiration, and therefore photosynthesis, for a longer time between rain events (Morgan et al 2004;Keel et al 2007;Leuzinger and Körner 2007;Holtum and Winter 2010;Leuzinger and Körner 2010;Macinnis-Ng et al 2011). Such water savings could also facilitate microbial activity and nutrient provision, and enable turgor pressure in meristem tissues to remain above the critical threshold required for cell expansion (Boyer 1968;Eamus et al 1995), thereby facilitating growth. Second, elevated c a could increase the NSC pool, which, in turn, could be used to sustain plant metabolism for longer periods following stomatal closure and cessation of A in response to drought, according to the carbon-centric perspective (Sala et al 2012).…”
Section: Effects Of Elevated C a On Resistance To Droughtmentioning
confidence: 99%
“…This could lead to a reduction in soil water depletion due to reduced canopy-scale transpiration, which could sustain transpiration, and therefore photosynthesis, for a longer time between rain events (Morgan et al 2004;Keel et al 2007;Leuzinger and Körner 2007;Holtum and Winter 2010;Leuzinger and Körner 2010;Macinnis-Ng et al 2011). Such water savings could also facilitate microbial activity and nutrient provision, and enable turgor pressure in meristem tissues to remain above the critical threshold required for cell expansion (Boyer 1968;Eamus et al 1995), thereby facilitating growth. Second, elevated c a could increase the NSC pool, which, in turn, could be used to sustain plant metabolism for longer periods following stomatal closure and cessation of A in response to drought, according to the carbon-centric perspective (Sala et al 2012).…”
Section: Effects Of Elevated C a On Resistance To Droughtmentioning
confidence: 99%
“…At the same time, total plant biomass in these species significantly increased by 27%-67% (Eamus et al, 1995;Lee and Jarvis, 1996;Kinney and Lindroth, 1997;Curtis and Wang, 1998;Tomlinson and Anderson, 1998;Huxman et al, 1999;Thomas et al, 1999;Hattenschwiler, 2001;Tognetti et al, 2002;Rey and Jarvis, 2003). However, it is unclear whether plant organs or root hydraulic conductance initially responds to elevated levels of CO 2 and how plant organ development interacts with the conductance when a species acclimatizes to the increase in CO 2 .…”
Section: Introductionmentioning
confidence: 89%
“…Many studies have shown that after 4 months to 4.5 years of exposure to high levels of CO 2 , root hydraulic conductance decreased in the seedlings of Maranthes corymbosa and Eucalyptus tetrodonta (Eamus et al, 1995), Helianthus annuus (Huxman et al, 1999), Erica arborea, Myrtus communis and Juniperus communis , Fagus sylvatica, Abies alba, Acer pseudoplatanus, Quercus robur, Taxus baccata (Hattenschwiler, 2001) and in Betula pendula saplings (Rey and Jarvis, 2002), but increased in Salix sagitta seedlings (Johnson et al, 2002). At the same time, total plant biomass in these species significantly increased by 27%-67% (Eamus et al, 1995;Lee and Jarvis, 1996;Kinney and Lindroth, 1997;Curtis and Wang, 1998;Tomlinson and Anderson, 1998;Huxman et al, 1999;Thomas et al, 1999;Hattenschwiler, 2001;Tognetti et al, 2002;Rey and Jarvis, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We test the impact of acclimation of two leaf physiology parameters, k L and f . A number of studies have found decreases in the leaf-specific hydraulic conductance (k L ) in plants grown in eC a (Atkinson and Taylor, 1996;Eamus et al, 1995;Eguchi et al, 2008;Heath et al, 1997), with reductions in a wide range of 10-100 %. Berryman et al (1994) found a higher sensitivity of g s to decreasing water content of excised leaves in Maranthes corymbosa, which can be interpreted as a less negative f in the Tuzet model (Eq.…”
Section: Effect Of Acclimation Of Leaf Parameters On C a × Drought Inmentioning
confidence: 99%
“…A simple prediction for this interaction is that the C a response will be higher under soil drought for two reasons: firstly, lower leaflevel water use under eC a (Eamus, 1991;Medlyn et al, 2001) leads to higher soil water content, which helps plants avoid soil water deficits; and secondly, lower intercellular CO 2 concentration (C i ) during drought enhances the C a response because of the non-linear response of photosynthetic rate to C i (Grossman-Clarke et al, 2001;McMurtrie et al, 2008). While both mechanisms have been confirmed in a number of crop and grassland studies (e.g.…”
Section: Introductionmentioning
confidence: 99%